Aluminium cast house technology XII : selected, peer reviewed papers from the 12th international conference and exhibition, on aluminium cast house technology, September 11-14, 2011, Melbourne, Australia - Taylor, John A. (John Alexander), 1969-; Grandfield, John F.; Prasad, A. (Arvind) (Materials science forum ;, 2011)
The Aluminum Cast House Industry recognises the importance of technology management in reducing operating costs and making high-quality products safely; with minimal environmental impact. The 12th Aluminium Cast House Technology Conference and Exhibition provided a unique venue where researchers, producers and suppliers could present and discuss the latest ideas in the science and technology of casting aluminium-alloy semi-finished products. The proceedings, with 29 peer-reviewed papers, offer invaluable insights into the subject. Review from Book News Inc.: Researchers, producers, and suppliers discuss the science and technology of casting aluminum alloy semi-finished products. A cast house is where such casting takes place, not a metal domicile. The 29 papers cover markets and cast house layouts, controlling melt loss, furnaces and refractories, safety, melt quality and treatment, direct chill casting, ingot and continuous casting, and alloys and heat treatment. Among the topics are preserving metal units utilizing the latest generation of aluminum dross press, thermocouple protection tube options for aluminum casthouses, developing a fused magnesium chloride containing refining flux based on a ternary system, the automatic control of molten metal flow for improving casting performance, and the metallurgy of homogenization. (Annotation ³2011 Book News Inc. Portland, OR).